EFEKTIFITAS METODE LANGSUNG DALAM PENGAJARAN KETERAMPILAN BERBICARA BAHASA ARAB - Lina Marlina (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2016)
Direct Method has currently become an alternative approach in teaching Arabic, to upgrade students' speaking ability. With this method, there will be direct communications in Arabic between teachers and students. In such condition, students will practice almost similar to their original (mother) language in a 2-way effective communication approach. The method was developed by experts of Arabic teaching following a disappointment to the result of teaching Arabic utilizing the approach of grammatical translation especially in relation to the critical needs of the active Arabic. In practice, the Direct Method shows its advantages. However at the same time the method produces challanges to teachers to improve their skills in applying the method properly. Skills and experiences of teachers in teaching with the direct method become very critical to overcome the challanges. The more skills and experiences the teachers, the easier and must be the better for them to overcome the challanges.